Above the Law’: Changes in Methamphetamine Laws and the Deterrent Impact on Market-Involved Women - Carbone-Lopez, Kristin (American journal of criminal justice, 2015)
Growing concern over the use and manufacture of methamphetamine in the United States prompted federal and state legislatures to more strictly regulate precursor agents and to increase penalties for its possession. While criminologists are generally skeptical of the deterrent effect of increased sanctions on crime rates, there is some evidence at the macro-level that these legislative changes have been effective. There is less clear-cut evidence of the micro-level impact of such laws. Drawing from interviews with 38 women methamphetamine users in Missouri, I explore the impact of recent changes in methamphetamine-related laws on their use and market behavior. The results provide insight into how law filters down to the individual level, including the relevance of accurate understanding of laws, and may give some indication as to the potential effectiveness of increasingly punitive policies.